Elaboration and evaluation of judo training means - Ferreira Pedrosa, G.; Mota Soares, Y.; Gonçalves, R.; Pena Couto, B.; Dias da Silva, R. A.; Szmuchrowski, L. A. (Archives of Budo, 2015)
Background and Study Aim. At the moment to select training means for composing the training program, many coaches are guided by the empirical evidence of training means specificity. A practical and scientific instrument containing relevant judo training means may contribute to coaches to achieve better results. The purpose of this study was to elaborate a catalogue of judo training means and classify it according to specificity: general, special or specific. Material and Methods. Five Brazilian judo coaches answered what exercises are used for training the judo demand. The exercises were combined to a physical training method generating training means and it were submitted to 9 experts who evaluated the practical relevance and the specificity of each training mean to form the catalogue. The Coefficient of Validity Content and the Coefficient of Kappa were used as a statistical tool to measure the practical relevance of the catalogue and the classification of specificity, respectively. Results. Seventy six exercises were listed and suitable to training means. Coefficient of Kappa value was = 0.533. Twenty two training means were classified as general, sixteen as special and thirty eight as specific of judo. The Coefficient of Validity Content for the catalogue was = 0.821. Analyzing this coefficient by specificity, the group of specific training means achieved the higher rate and the general group had the lower rate. Conclusion. A catalogue of training means for judo were elaborated and classified by specificity. The high rate found for practical relevance confirm the representatively of this catalogue.